Subadult ravens generally don't transfer valuable tokens to conspecifics when there is nothing to gain for themselves - Massen, Jorg J.; Lambert, Megan; Schiestl, Martina; Bugnyar, Thomas (Frontiers in Psychology, 2015)
The extent to which humans help each other is extraordinary in itself, and difficult to explain from an evolutionary perspective. Therefore, there has been a recent surge in studies investigating the evolution of prosocial behavior using a comparative approach. Nevertheless, most of these studies have focused on primates only, and little is known about other animal orders. In a previous study, common ravens (Corvus corax) have been shown to be indifferent to the gains of conspecifics. However, this may have been due to the experimental set-up, as many studies that use different set-ups report conflicting results within the same species. We therefore tested ravens’ prosocial tendencies in a different set-up; i.e., we tested whether sub-adult ravens would transfer a token to a partner and, thereby, provide the partner with the opportunity to exchange a token for a reward. To control and test for effects of partner identity, we tested 8 individuals both in a dyadic and in a group setting. Our results show that in general the ravens in our experiment did not show other-regarding preferences. However, some acts of helping did occur spontaneously. We discuss what could be the causes for those sporadic instances, and why in general prosocial tendencies were found to be almost lacking among the ravens in this set-up.